1973
DOI: 10.1113/jphysiol.1973.sp010414
|View full text |Cite
|
Sign up to set email alerts
|

The regional distribution of emotional sweating in man

Abstract: SUMMARY1. Emotional sweating was induced in normal subjects by mental arithmetic at environmental temperatures of 29 and 260 C and estimated from continuous records of body weight loss.2. The sweat output from four independent regions of the body -(a) the head and neck, (b) the arms and legs, (c) the trunk, and (d) the hands and feet -was studied separately, the remainder of the body being covered in each case by plastic bags. The evaporative water loss from each skin region increased markedly during mental ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
1

Year Published

1975
1975
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(37 citation statements)
references
References 9 publications
1
35
0
1
Order By: Relevance
“…Therefore, these recordings merely demonstrate changes in EDA under different stressors. Emotional sweating (increased sweat gland activity as a concomitant of psychological, and especially, emotional states) has been observed mainly on palmar and plantar sites, but the specificity of emotional sweating remains in question [37]. Our findings indicate that the ventral sides of the distal forearms can also produce sweat responses to emotional stimuli.…”
Section: Discussionmentioning
confidence: 63%
“…Therefore, these recordings merely demonstrate changes in EDA under different stressors. Emotional sweating (increased sweat gland activity as a concomitant of psychological, and especially, emotional states) has been observed mainly on palmar and plantar sites, but the specificity of emotional sweating remains in question [37]. Our findings indicate that the ventral sides of the distal forearms can also produce sweat responses to emotional stimuli.…”
Section: Discussionmentioning
confidence: 63%
“…Even in a temperate environment, however, neural impulses for thermal sweating still reach the sweat glands and mental effects can be visualized on a focal area where local sweating has been provoked by a suforific agent (KENNARD, 1963;OGAWA, 1970;OGAWA and BULLARD, 1972). Furthermore, a small number of functional sweat glands have been detected on the general body surface in a temperate environment (RANDALL, 1946;NAKAYAMA and ARIMURA, 1955), and it has also been reported that there are no significant regional differences in sweat responses to emotional stimuli within the comfort zone (ALLEN et al, 1973). At a lower temperature, sweat response of the palm is no longer noted (KuNo, 1956), or no neural impulse reaches the sweat glands of the general body surface (OGAWA and BULLARD, 1972).…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, the glands of the palms and soles were thought to respond only to mental stimuli and the glands of the rest of the body only to thermal stimuli (Kuno, 1956). However, Allen, Armstrong & Roddie (1973) showed that sweat glands of all regions responded * M.R.C. Scholar.…”
Section: P Physiological Society September 1978mentioning
confidence: 99%